2011
DOI: 10.1152/ajpendo.00121.2011
|View full text |Cite
|
Sign up to set email alerts
|

Decreased plasma ghrelin contributes to anorexia following novelty stress

Abstract: We hypothesized that anorexia induced by novelty stress caused by exposure to a novel environment may be due to activation of corticotropin-releasing factor (CRF) and subsequently mediated by decreasing peripheral ghrelin concentration via serotonin (5-HT) and melanocortin-4 receptors (MC4R). Each mouse was transferred from group-housed cages to individual cages to establish the novelty stress. We observed the effect of changes in feeding behavior in a novel environment using the method of transferring group-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 56 publications
1
100
0
Order By: Relevance
“…53) We have recently determined that CRFR1 is also involved in the regulation of ghrelin secretion. Using a novelty stress model, 54) we found that 3 h after the novelty stress, appetite reduction was associated with a decrease in the plasma ghrelin level. 55) Administering a CRF1R selective antagonist, but not a CRF2R antagonist, resolved the reduction in food intake 3 h after the novelty stress by enhancing circulating ghrelin concentrations.…”
Section: Animal Studiesmentioning
confidence: 89%
See 1 more Smart Citation
“…53) We have recently determined that CRFR1 is also involved in the regulation of ghrelin secretion. Using a novelty stress model, 54) we found that 3 h after the novelty stress, appetite reduction was associated with a decrease in the plasma ghrelin level. 55) Administering a CRF1R selective antagonist, but not a CRF2R antagonist, resolved the reduction in food intake 3 h after the novelty stress by enhancing circulating ghrelin concentrations.…”
Section: Animal Studiesmentioning
confidence: 89%
“…Interestingly, 5-HT 1B and 5-HT 2C receptor antagonists and melanocortin-4 (MC4) receptor antagonist alleviated the novelty stress-induced hypophagia and the reduction in circulating ghrelin levels. 55) Moreover, intracerebroventricular administration of the 5-HT 1B/2CR agonist mCPP suppressed the plasma acylated ghrelin level and food intake. 55) From these results, we hypothesize that acute appetite suppression due to CRF1R activation after a novelty stress is caused by a chain reaction of appetite control mechanisms mediated by 5-HT 1B/2C receptors in the arcuate nucleus to MC4 receptor system in the paraventricular nucleus, causing lowered peripheral ghrelin secretion.…”
Section: Animal Studiesmentioning
confidence: 97%
“…reported that the serum ghrelin level decreased after 7 days of novelty stress. [43] They suggested the increases in CRH resulted in a declined ghrelin level, leading to the sustained food intake reduction. [43] However, other researches indicated an opposite finding between the ghrelin level and food intake.…”
Section: Discussionmentioning
confidence: 99%
“…[43] They suggested the increases in CRH resulted in a declined ghrelin level, leading to the sustained food intake reduction. [43] However, other researches indicated an opposite finding between the ghrelin level and food intake. [444546] Some previous studies demonstrated that the elevated serum ghrelin level helps to an individual for adaptation to chronic stress but at the expense of increased eating food.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammatory stress elicited by adjuvant-induced arthritis in rats or rheumatoid arthritis in humans reduces circulating ghrelin levels (59). There are also reports that a psychological stressor such as novelty stress in mice decreases plasma levels of ghrelin and food intake, alterations prevented by rikkunshito (60, 61). Chronic restraint stress or exposure to foot-shock downregulates ghrelin mRNA expression in the mouse hypothalamus (62) and reduces plasma levels of ghrelin in rats (63).…”
Section: Modulation Of Gut-brain Signaling Under Conditions Of Stressmentioning
confidence: 99%